Human–machine interaction control for stochastic cell manipulation systems. (September 2021) - Ta, Quang Minh; Cheah, Chien Chern
Abstract: While many physical robot systems are able to work cooperatively with humans to perform numerous tasks, existing optical cell manipulation systems can only perform either manual or automated tasks at a time. As optical cell manipulation is essentially different from robotic manipulation in the physical world due to its stochastic nature, existing human–robot interaction control techniques cannot thus be directly reproduced into optical micro-manipulation of cells. This paper proposes a human–machine interaction control approach for stochastic optical cell manipulation systems. A theoretical foundation is then developed, and thus enabling human to interpose or interact, when applicable or needed, with an automated cell manipulation system without interrupting the manipulation process. Therefore, it offers an opportunity for human to get involved with an automated cell manipulation system so as to deal with unexpected events or complex tasks, rather than to stop or restart the whole manipulation process. Both the capacity of an automated control system – which provides precise and productive cell manipulation, and human ability – in terms of decision making, if needed, are then consolidated into a single optical cell manipulation system. Rigorous mathematical formulation is developed with the consideration of the stochastic perturbations, and the stability of the human–machine interaction control system is analyzed from a stochastic perspective. Experiments are then performed to illustrate the effectiveness of the proposed approach.